English medium instruction and idiomaticity in English as a Lingua Franca - Briggs, JG; Smith, SA (Urmia University Press, 2017)
This paper critically considers the implications of the growth of English-medium instruction (EMI) globally for idiomaticity in English as a Lingua Franca (ELF). We first make the case for idiomaticity in English in terms of its contribution to language processing and use and regarding the challenges and affordances it presents to users of English as a second/additional language. We then compare the domains of ELF and EMI in order to pinpoint the similarities and differences between their characteristics, with specific reference to the role of idiomaticity. We argue that EMI prepares students for academic ELF, which is idiomatically distinct from academic L1-English and non-academic varieties of English; that the unidirectional nature of much EMI discourse has implications for ELF-specific idiomaticity; and that the large-scale, long-term language contact engendered by the growth of EMI denotes that an increasing number of L2-English users may be underprepared for a wealth of ELF events, particularly those which draw more substantively on idiomaticity or are themselves idiosyncratically idiomatic. We consider how EMI pedagogy might foster students’ idiomatic competence and creativity to take account of their ELF needs beyond the ivory tower.